Reliability of a submaximal field test in wheelchair rugby - Grossmann, F.; Perret, C.; Roelands, B.; Meeusen, R.; Flueck, J. L. (International Journal of Sports Medicine, 2023)
The aim was to investigate the test-retest reliability of performance and physiological variables of a submaximal wheelchair rugby field test. Eight trained wheelchair rugby athletes with a spinal cord injury (age: median 40, interquartile range 6.9 y; body mass: median 77.7, interquartile range 23.9 kg) performed a submaximal field test two times with a duration of 41 min, split up into four sets of eight min. Each set included eight laps with one eight-meter sprint (SP8) and one four-meter sprint (SP4). The absolute and relative reliability and the performance decrease (fatigue) across the sets were investigated. The examined variables were sprinting time, heart rate, and RPE. The measured parameters showed moderate (peak heart rate ICC3,1=0.663, peak rate of perceived exertion ICC3,1=0.718), good (SP4 ICC3,1=0.874), and excellent (mean heart rate ICC3,1=0.905, SP8 ICC3,1=0.985) test-retest reliability. Fatigue was observed for SP8 in test 2 between set 2/3 and set 2/4. For test 1 a significant decrease of performance for SP4 was found between set 2/3, set 2/4 and between set 3/4. In conclusion the submaximal field test showed moderate to excellent reliability for all measured parameters. The observed fatigue seems to be not clinically relevant. The test can be recommended to assess the effects of training or interventions.